2019
DOI: 10.3390/agronomy9110733
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Compensates Phosphorus Deficit-Induced Growth Inhibition by Improving Photosynthetic Capacity, Antioxidant Potential, and Nutrient Homeostasis in Tomato

Abstract: Phosphorus (P) deficiency in soils is a major problem for sustainable crop production worldwide. Silicon (Si) is a beneficial element that can promote plant growth, development and responses to stresses. However, the effect of Si on tomato (Solanum lycopersicum L.) growth, photosynthesis and mineral uptake under P deficit conditions and underlying mechanisms remain unclear. Here, we showed that low P (LP) supply inhibited tomato growth as revealed by significantly decreased fresh and dry weights of shoots and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Organic pools of P in plant tissues mainly exist as nucleic acids, phospholipids, phosphorylated proteins and P-ester metabolites 15 . Under P deficiency, phospholipids have greater potential to serve as an alternate source of P which remobilizes towards young growing plant tissues 46 . This phenomenon of replacing phospholipids in cell membranes with sulfolipids and galactolipids is known as membrane-lipid remodeling 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Organic pools of P in plant tissues mainly exist as nucleic acids, phospholipids, phosphorylated proteins and P-ester metabolites 15 . Under P deficiency, phospholipids have greater potential to serve as an alternate source of P which remobilizes towards young growing plant tissues 46 . This phenomenon of replacing phospholipids in cell membranes with sulfolipids and galactolipids is known as membrane-lipid remodeling 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The judicious application of silicon, phosphorus, and plant growth promoting rhizobacteria is considered pivotal in the mitigation of such abiotic stresses [ 43 ]. It has been reported that Si maintains plant strength through the regulation of the internal physiology [ 50 ] and compensating P deficiencies in plants [ 51 ]. It has also been reported that PGPB engineers the root system of plants, thereby facilitating nutrient uptake [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excess-P stress is also observed in some greenhouse soils subjected to heavy application of P fertilizer or in hydroponic culture where a high P concentration is supplied [ 9 ]. The beneficial effect of Si on P deficiency or excess stress has been reported for a number of plant species [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. To the best of our knowledge, however, no review has discussed the roles and mechanisms of Si in alleviating P-imbalance stress in plants.…”
Section: Introductionmentioning
confidence: 99%